The Role of Traditional Media in political changes - محمد , أسامة; عوض, بشرى رفيق (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research has attempted to define the role traditional media in political changes, especially such media are greatly a significant means of contact between society and the individuals and a source of education and knowledge. Moreover, the research has tackled the most effective theories of traditional media, and thrown light on both their negative and positive aspects. Aside of realizing the political role of Mass Media and how they contribute to the portrayal of change aspects since they are a participating tool in actual grounds, there is a connection between the political process and the informational one: The relation between the two differs due to the change in the current system and the level of democracy in each country. He research has recognized a lot of obstacles which detain the development of political media in some Arab country, such as absence of neutrality since it attempts to support a certain political system, the lack peoples participation in decision making, the dependence of media on imported equipment, and the attempts of the west to marginalize the Arab,s media and to to drive it get involved in trivial issues.